The effect of a specific high intensity warm-up on simulated mixed teams relay triathlon performance - Palmer, R. R.; Eastwood, A.; D`Auria, S.; Reaburn, P. J. (Journal of Australian Strength and Conditioning, 2019)
An individualised, high intensity intermittent triathlon specific pre-race warm-up may improve running and overall performance compared to a moderate aerobic or plyometric based warm-up.